Analysis Of Students’ Psychological Factors During Thesis Consultation In IAIN Bukittinggi - Sesmiarni, Zulfani (International Journal of Psychosocial Rehabilitation, 2020)
This research is aimed to know students’ psychological factors during thesis consultation session. Research population was students who had did thesis consultation on 2019 totaling 1180 people, meanwhile sample was chosen by accidental sampling by 15 %, totaling 172 people. Research data analysis used descriptive quantitative. Based on the result of the research, it is known prominent psychologis aspect on students before thesis consultation is afraid and worried however after thesis consultation session, they felt joy and satisfied with thesis consultation with their supervisor. It is illustrated from students’ response who argued appointed supervisor has very good competence. In addition, lecturer has scientific level and good interaction during thesis consultation. Moreover, lecturer had taken the time to always present at the appointed time for consultation. Generally, the response of students who had thesis consultation was satisfied with student’s thesis consultation service. Response of student, they truly felt joy and get many knowledge about scientific work after thesis consultation